Carbon nanofiber based on silk protein fiber, preparation method and application thereof
By adding MXene two-dimensional nanomaterials to silk protein nanofibers, the problem of reaction conditions control and morphological stability in carbon nanofiber synthesis is solved, and the efficient preparation of carbon nanofibers and the flexibility and high electrochemical energy storage performance of the electrode materials are achieved.
Patent Information
- Application Number
- CN202510027213.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-08
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-01-08
AI Technical Summary
The existing carbon nanofiber synthesis technology has problems such as difficult to accurately control the reaction conditions, uneven distribution of carbon nanofiber diameter and length, and low safety.
The MXene two-dimensional nanomaterial with thermal stability is added to the silk protein nanofiber, and the morphology is maintained through mixing with the silk protein fiber and high-temperature carbonization to avoid melt polymerization.
The diameter of carbon nanofibers is adjustable, simple operation, high safety, and has obtained a spongy carbon nanofiber electrode material with flexibility and good electrochemical energy storage performance.
Smart Images

Figure CN119465447B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of carbon nanofiber materials, and in particular to a carbon nanofiber based on silk protein fiber, a preparation method and application thereof. Background Art
[0002] Carbon Nanofibers (CNF) materials have great application potential in electronics, energy, environmental protection, biomedicine and other fields due to their low toxicity, good mechanical strength, high conductivity and other properties. However, the synthesis and production of carbon nanofibers using traditional non-renewable resources such as fossil fuels as raw materials is not suitable for the sustainable development needs of today's society. Biomass materials are widely used in various carbon materials, such as the production of porous carbon electrode materials, due to their wide sources, low prices and renewability. Therefore, exploring other renewable resources as raw materials and developing methods for preparing carbon nanofibers has become a hot topic in the current scientific research field.
[0003] The current methods for synthesizing carbon nanofibers mainly include chemical vapor deposition, electrospinning, and hydrothermal carbonization. Chemical vapor deposition uses cheap hydrocarbon compounds and biomass materials as carbon sources, and synthesizes carbon nanofibers by pyrolysis or catalytic decomposition under the action of metal catalysts (such as iron, cobalt, nickel, etc.). The carbon nanofibers prepared by this method have high crystallinity and good conductivity. However, due to the large number of reaction conditions involved (such as temperature, pressure, type and concentration of catalysts, etc.) and the need for a large amount of energy to maintain high temperature or high pressure conditions, it is difficult to accurately control the pyrolysis or catalytic process, which leads to uneven distribution of diameter and length of carbon nanofibers. Electrospinning is a technology that uses electrostatic field forces to convert polymer solutions or melts into nanofibers. Although many researchers have used a variety of materials (lignin, cellulose, etc.) to prepare carbon nanofibers, they usually need to be extracted first and then mixed with polymers (such as polyacrylonitrile) before spinning. In addition, a very high voltage (10~20kV) needs to be applied during spinning, which makes it less safe. In addition, its morphology and structure will also be affected by various conditions (carbonization temperature, carbonization time, etc.) in the subsequent carbonization process. Hydrothermal carbonization refers to the process of generating carbon nanofibers in a hydrothermal reactor, using organic sugars or carbohydrates as raw materials and water as the reaction medium, at a certain temperature and pressure, through a series of reactions (such as hydrolysis, dehydration, decarboxylation, aromatization and re-condensation, etc.). These reactions occur sequentially, but may also occur simultaneously, and have different kinetic characteristics. Therefore, the reaction mechanism of the hydrothermal carbonization method is complex and is affected by a variety of process parameters, which makes the optimization and control of reaction conditions complicated. In addition, the diversity of its by-products also increases the difficulty of subsequent purification. In summary, at the current stage of synthetic technology, to prepare ideal carbon nanofibers, not only has strict requirements on the precision of experimental equipment, but also faces huge challenges in the precise control of reaction conditions. Therefore, it is particularly urgent and important to develop a simple and efficient method for preparing carbon nanofibers.
[0004] Silk is a natural protein with a fine hierarchical structure assembled from nanofibers. It has good flexibility, fine porous structure and excellent mechanical strength. It is of great significance to prepare carbon nanofibers by simple methods using silk, a huge biomass material. However, the method of directly carbonizing silk protein nanofibers (SNF) is difficult to maintain the original nanofiber shape to form carbon nanofibers due to melt polymerization during the carbonization process. Therefore, thermally stable substances are needed to prevent them from aggregating together, and modification research to maintain their stable morphology is urgently needed. Summary of the invention
[0005] MXene, as a two-dimensional transition metal compound, has excellent hydrophilicity, good mechanical properties and thermal stability. Adding MXene to silk protein nanofibers can be well mixed with silk protein fibers and maintain its morphology stability during high-temperature carbonization.
[0006] In order to solve the above problems, the present invention adds thermally stable MXene two-dimensional nanomaterials into silk protein nanofibers (SNF) to avoid the problem of melt polymerization during carbonization of silk protein nanofibers, and provides a carbon nanofiber based on silk protein fibers, a preparation method and its application.
[0007] In order to achieve the above object, the present invention discloses a method for preparing carbon nanofibers based on silk protein fibers, comprising the following steps:
[0008] S1, adding Ti3C2T x After MXene, the mixture was stirred under argon gas and ice bath to obtain a mixed solution;
[0009] S2, freeze-drying the mixed solution obtained in step S1 to obtain silk protein nanofiber-X% (SNF-X%), wherein X% is Ti3C2T x MXene to silk protein nanofiber mass ratio;
[0010] S3, carbonizing the SNF-X% obtained in step S2 to obtain carbon nanofiber-X% (CNF-X%).
[0011] In step S1, the concentration of the silk protein nanofiber solution is 5-15 mg mL -1 , the ice bath time is 20min.
[0012] In the step S1, X=2.08~6.25.
[0013] In step S1, the stirring speed is 10000-15000 rpm, and the stirring time is 8-12 min.
[0014] In step S1, the method for preparing silk protein nanofibers comprises the following steps:
[0015] P1, 15 g of silkworm cocoons were added to 8 mol / L urea solution and soaked at 80 °C for 3 h. After soaking, the silk was washed with deionized water until the solution was neutral. The treated silk was dried at 50 °C for 12 h.
[0016] P2, mixing choline chloride and malonic acid in a molar ratio of 1:1, heating at 80 °C to obtain a transparent and uniform liquid, i.e., a deep eutectic solvent;
[0017] P3, add dried silk to the deep eutectic solvent and stir it at 100 °C for two weeks until a brown-yellow viscous liquid is obtained;
[0018] P4, the brown-yellow liquid is centrifugally washed with ethanol and deionized water to obtain a silk protein nanofiber solution, which is off-white.
[0019] In step S1, Ti3C2T x The preparation method of MXene is as follows: 0.5 g LiF powder and 0.5 g Ti3AlC2 powder are slowly added to HCl solution, and then the mixed solution is stirred in an oil bath at 35 °C; the reactants are centrifuged and washed with deionized water until the pH is 6, and then the obtained solution is ultrasonically treated to obtain exfoliated and dispersed Ti3C2T x The suspension solution was then concentrated by high-speed centrifugation to prepare Ti3C2T x MXene solution.
[0020] In step S2, the freeze-drying time is 48 h.
[0021] In step S3, the carbonization treatment temperature is 800°C, the carbonization treatment heating rate is 15°C / min, the atmosphere is argon, and the insulation time is 2 h.
[0022] The invention also discloses carbon nanofibers based on silk protein fibers prepared by the above preparation method and application of the carbon nanofibers based on silk protein fibers in electrode materials.
[0023] Compared with the prior art, the beneficial effects of the present invention are:
[0024] 1. The present invention uses two-dimensional nanomaterial MXene as an additive, separates silk protein nanofibers, prevents the fibers from melt polymerization during the carbonization process, and successfully develops a method for preparing carbon nanofibers using silk as biomass raw material;
[0025] 2. The diameter of the carbon nanofibers in the present invention can be controlled by changing the proportion of the added MXene;
[0026] 3. The present invention is easy to operate, and silk is widely available as a raw material. It is easy to operate, does not require strong acids, strong bases or corrosive chemical reagents, and does not generate toxic byproducts.
[0027] 4. The present invention obtains a sponge-like carbon nanofiber electrode material with a certain flexibility, which does not require the addition of additional conductive agents and adhesives and exhibits good electrochemical energy storage performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 Ti3C2T x Schematic diagram of the process of preparing carbon nanofibers using MXene as an additive and silk as a biomass raw material;
[0029] Figure 2 The scanning electron microscope (SEM) images are of SNF -X%, X%=0%;
[0030] Figure 3 This is the scanning electron microscope (SEM) image of SNF -X%, X%=1.56%;
[0031] Figure 4 This is the scanning electron microscope (SEM) image of SNF -X%, X%=2.08%;
[0032] Figure 5 This is the scanning electron microscope (SEM) image of SNF -X%, X%=3.13%;
[0033] Figure 6 This is the scanning electron microscope (SEM) image of SNF -X%, X%=6.25%;
[0034] Figure 7 Scanning electron microscope (SEM) images of CNF - X%, X%=0%;
[0035] Figure 8 The scanning electron microscope (SEM) image of CNF - X%, X% = 1.56%;
[0036] Fig. 9 The scanning electron microscope (SEM) image of CNF - X%, X% = 2.08%;
[0037] Fig.10 The scanning electron microscope (SEM) image of CNF - X%, X% = 3.13%;
[0038] Fig.11 The scanning electron microscope (SEM) image of CNF - X%, X%=6.25%;
[0039] Fig.12 is the distribution histogram of CNF -X% diameter;
[0040] Fig.13 Symmetric supercapacitor composed of CNF-X% in 6 M KOH electrolyte at 100 mV s -1The CV curve comparison chart below;
[0041] Fig.14 The mass specific capacitance data of the symmetrical supercapacitor composed of CNF-X% at different scanning speeds. DETAILED DESCRIPTION
[0042] The above and other technical features and advantages of the present invention are described in more detail below in conjunction with the accompanying drawings.
[0043] Example 1
[0044] Preparation of silk protein nanofibers:
[0045] 15 g of silkworm cocoons were added to 8 M CO(NH2)2 urea solution and soaked at 80 °C for 3 h. The silk was then washed with deionized water until the washed solution was neutral, and the treated silk was dried at 50 °C for 12 h. Choline chloride and malonic acid were mixed in a molar ratio of 1:1 and heated at 80 °C to obtain a transparent and uniform liquid, namely the deep eutectic solvent. Subsequently, the treated silk was added to the deep eutectic solvent in a ratio of silk mass: deep eutectic solvent mass = 1:40, and stirred at 100 °C for about two weeks until a brown-yellow viscous liquid was obtained. The brown-yellow liquid was then centrifuged and washed with ethanol and deionized water to obtain a silk protein nanofiber SNF solution, which was off-white (such as Figure 1 as shown).
[0046] Example 2
[0047] Preparation of Ti3C2T x MXene:
[0048] 0.5 g LiF and 0.5 g Ti3AlC2 powder were weighed and slowly added into 9 M HCl (5 mL) solution. The mixed solution was then stirred in an oil bath at 35 °C. After 48 h, the reactants were centrifuged and washed with a large amount of deionized water several times until the pH value was 6. The obtained solution was then ultrasonically treated to obtain exfoliated and dispersed Ti3C2T x The suspension solution is then concentrated by high-speed centrifugation to prepare a high-concentration Ti3C2T x Solution.
[0049] Example 3
[0050] Preparation of carbon nanofiber material (CNF - X%, X%=0%):
[0051] Adjust the concentration of the solution containing 700 mg SNF to 5-15 mg mL -1, ice bath for 20 min, add 0 mg Ti3C2T x MXene, and stirred at a speed of 10000-15000 rpm for 8 min under the conditions of argon and ice bath, and the resulting mixture solution was freeze-dried to obtain SNF-0% after 48 h. SNF-0% was carbonized at 800 °C to obtain CNF-0%. The carbonization heating rate was 15 °C / min, the atmosphere was argon, and the insulation time was 2 h. The obtained carbon nanofiber material was sponge-like (such as Figure 1 as shown).
[0052] Example 4
[0053] Preparation of carbon nanofiber material (CNF - X%, X%=1.56%):
[0054] The difference between this embodiment and embodiment 3 is that the added Ti3C2T x The MXene content was 10.94 mg, and the other process conditions were the same as those in Example 3. The final CNF content was -1.56%.
[0055] Example 5
[0056] Preparation of carbon nanofiber material (CNF - X%, X%=2.08%):
[0057] The difference between this embodiment and embodiment 3 is that the added Ti3C2T x The MXene content was 14.58 mg, and the other process conditions were the same as those in Example 3. The final CNF content was -2.08%.
[0058] Example 6
[0059] Preparation of carbon nanofiber material (CNF - X%, X%=3.13%):
[0060] The difference between this embodiment and embodiment 3 is that the added Ti3C2T x The MXene content was 21.88 mg, and the other process conditions were the same as those in Example 3. The final CNF content was -3.13%.
[0061] Example 7
[0062] Preparation of carbon nanofiber material (CNF - X%, X%=6.25%):
[0063] The difference between this embodiment and embodiment 3 is that the added Ti3C2T xThe MXene content was 43.75 mg, and the other process conditions were the same as those in Example 3. The final CNF content was -6.25%.
[0064] Silk was degummed with urea solution to obtain silk fibers. After being treated with deep eutectic solvent, the silk protein nanofibers in the silk fibers were continuously stripped out. This is because the deep eutectic solvent is mainly composed of hydrogen bond acceptors (choline chloride) and hydrogen bond donors (malonic acid). When they are mixed in a molar ratio of 1:1, at a temperature of 80 °C, the two solids will gradually become transparent and colorless liquids, and there is a strong hydrogen bond between the two substances. Therefore, when silk fibers are added, the deep eutectic solvent will affect the hydrogen bonds inside the silk and continuously penetrate into the silk fibers. The silk protein nanofibers continue to expand and eventually fall off from the silk fibers, eventually forming a solution containing a large number of silk protein nanofibers. Since the silk protein nanofiber solution with MXene added needs to be stirred at high speed in the subsequent process, in order to prevent MXene from oxidizing during high-speed stirring, the silk protein nanofiber solution needs to be ice-bathed for 20 minutes and purged with argon before adding the MXene solution. Similarly, during high-speed stirring, purging argon and maintaining an ice bath are also to prevent MXene from being oxidized. After that, the carbon nanofiber CNF-X% was obtained after freeze-drying for 48 h and carbonization at 800 °C.
[0065] Depend on Figure 2-Figure 6 It can be seen that in the freeze-dried silk protein nanofiber sample SNF-0% without MXene, the fiber diameter is maintained between 20 nm and 200 nm, and the fibers are staggered. In the SEM images of other SNF-X% samples with MXene added, in addition to the staggered fibers, it can be seen that they are evenly distributed on the MXene sheet, that is, a uniform coating effect is achieved.
[0066] Depend on Figure 7 It can be seen that after high-temperature carbonization, SNF-0% without MXene became blocky carbon due to the melting phenomenon between fibers, and lost its original fibrous morphology. Due to the excellent thermal stability of MXene, its structure can remain unchanged under high temperature conditions, and the two-dimensional sheet structure of MXene can well coat SNF and space adjacent silk protein nanofibers. The SNF-X% sample with MXene added avoided the melting polymerization phenomenon between fibers during the subsequent high-temperature carbonization process, and better maintained the original fibrous morphology and transformed into carbon nanofibers.
[0067] In addition, the content of MXene also has an impact on the successful formation of carbon nanofibers and the resulting fiber diameter. Figure 8As shown in Figure 2, when X% = 1.56%, the amount of MXene added is low, and MXene can hardly provide separation protection for SNF. Most SNFs still aggregate together during the carbonization process, forming a phenomenon similar to that of SNF without MXene added. Figure 9-11 As shown in the figure, it can be clearly seen that carbon nanofibers and MXene begin to play their role of separation and protection. The diameter of carbon nanofibers is mainly concentrated between 20 nm and 100 nm, and tends to gradually decrease with the increase of MXene addition (as shown in the figure). Fig.12 As shown in Figure 2, when the MXene content increases, the average number of silk protein nanofibers between two MXene sheets decreases, and the probability of melt polymerization at high temperatures also decreases accordingly, so the corresponding carbon nanofiber diameter becomes smaller. Therefore, the diameter and number distribution of the generated carbon nanofibers can be controlled by controlling the MXene ratio.
[0068] Example 8
[0069] Preparation of supercapacitor electrodes:
[0070] CNF-X% (X% = 0%, 1.56%, 2.08%, 3.13%, 6.25%) were pressed at 1 MPa for 10 s on a tablet press, and then punched with a belt punch with a diameter of 9 mm to obtain the desired electrodes.
[0071] Example 9
[0072] Assembling the supercapacitor:
[0073] Add a filter paper with a diameter of 19 mm as a separator between the two electrode sheets, put it into the battery shell, add an appropriate amount of electrolyte, put in the gasket, spring and cover, seal it, and use a button battery packaging machine to package it into a button battery. The electrolyte used is 6 M KOH (aq).
[0074] The prepared CNF-X% (X% = 0%, 1.56%, 2.08%, 3.13%, 6.25%) materials were assembled into symmetrical supercapacitors and cyclic voltammetry (CV) tests were performed at different scan rates. Fig.13 and Fig.14It can be seen that the CV curve area and mass specific capacitance of the CNF-0% sample without MXene at a scan rate of 100 mV s⁻¹ are both minimum values; compared with the block structure formed after carbonization of the sample without MXene, the carbon nanofiber structure is preserved in the sample with MXene added, and the specific surface area is larger, which can provide more sufficient active sites for charge storage. Although the amount of MXene itself is small, it can also provide a certain capacitance. Therefore, the CV curve area and mass specific capacitance of the sample with MXene added are significantly better than those of CNF-0%. In addition, CNF-1.56%, which has the least amount of MXene added, has better electrochemical performance than CNF-0% due to partial fiber fusion and polymerization during the carbonization process, but it is significantly lower than CNF-2.08%, CNF-3.13%, and CNF-6.25%.
[0075] The above description is only a preferred embodiment of the present invention, which is only illustrative and not restrictive of the present invention. Those skilled in the art understand that many changes, modifications, and even equivalences may be made to the present invention within the spirit and scope defined by the claims of the present invention, but all of them will fall within the scope of protection of the present invention.
Claims
1. A method for preparing carbon nanofibers based on silk protein fibers, characterized in that: The following steps are involved: S1, adding Ti3C2T x After MXene, the mixture was stirred under argon gas and ice bath to obtain a uniform mixed solution; S2, freeze-drying the mixed solution obtained in step S1 to obtain silk protein nanofibers - X%, wherein X% is Ti3C2T x MXene to silk protein nanofiber mass ratio; S3, carbonizing the silk protein nanofibers -X% obtained in step S2 to obtain carbon nanofibers -X%; In step S2, X%=2.08%~6.25%.
2. The method for preparing carbon nanofibers based on silk protein fibers according to claim 1, characterized in that: In step S1, the concentration of the silk protein nanofiber solution is 5-15 mg mL -1 , the ice bath time is 20 min.
3. The method for preparing carbon nanofibers based on silk protein fibers according to claim 1, characterized in that: In step S1, the stirring speed is 10000-15000 rpm, and the stirring time is 8-12 min.
4. The method for preparing carbon nanofibers based on silk protein fibers according to claim 1, characterized in that: In step S1, the method for preparing the silk protein nanofiber solution comprises the following steps: P1, 15 g of silkworm cocoons were added to 8 mol / L urea solution and soaked at 80 °C for 3 h. After soaking, the silk was washed with deionized water until the solution was neutral. The treated silk was dried at 50 °C for 12 h. P2, mixing choline chloride and malonic acid in a molar ratio of 1:1, heating at 80 °C to obtain a transparent and uniform liquid, i.e., a deep eutectic solvent; P3, add dried silk to the deep eutectic solvent and stir it at 100 °C for two weeks until a brown-yellow viscous liquid is obtained; P4, the brown-yellow liquid is centrifugally washed with ethanol and deionized water to obtain a silk protein nanofiber solution, which is off-white.
5. The method for preparing carbon nanofibers based on silk protein fibers according to claim 1, characterized in that: In step S1, Ti3C2T x The preparation method of MXene is as follows: 0.5 g LiF powder and 0.5 g Ti3AlC2 powder are slowly added to HCl solution, and then the mixed solution is stirred in an oil bath at 35 °C; the reactants are centrifuged and washed with deionized water until the pH is 6, and then the obtained solution is ultrasonically treated to obtain exfoliated and dispersed Ti3C2T x The suspension solution was then concentrated by high-speed centrifugation to prepare Ti3C2T x MXene.
6. The method for preparing carbon nanofibers based on silk protein fibers according to claim 1, characterized in that: In step S3, the carbonization treatment temperature is 800°C, the carbonization treatment heating rate is 15°C / min, the atmosphere is argon, and the insulation time is 2 h.
7. A carbon nanofiber based on silk protein fiber, prepared by the preparation method according to any one of claims 1 to 6.
8. Use of the carbon nanofibers based on silk protein fibers as claimed in claim 7 in electrode materials.
Citation Information
Patent Citations
Silk nanofiber membrane, preparation method therefor, and application of silk nanofiber membrane in supercapacitor
CN108022761A
Collagenous fiber-based flexible pressure sensing material and preparation method thereof
CN112812332A